Oxigenoterapia de alto flujo en paciente masculino de 40 años con insuficiencia respiratoria aguda por Covid-19. - Araujo Muñoz, Maittee Mariuxi (2023)
This clinical case focuses on a 40-year-old patient who came to the emergency room for 3 days due to dyspnea, headache, elevated temperature and SatO2 of 72% with a possible diagnosis of Covid-19. In this case, invasive and non-invasive procedures are described for patients to improve their admission symptoms, diagnostic methods, treatment, discharge, and state of health from discharge to discharge date. In addition, all examinations and days of hospitalization of the patient are included, including clinical data and medical history. High-flow oxygen therapy for patients with Covid is the first procedure to be performed after a diagnostic, physical, and symptomatic analysis by a doctor who initiates the high-concentration oxygen therapy process through an interface that allows control by a respiratory therapist.